MRI‐determined liver proton density fat fraction, with MRS validation: Comparison of regions of interest sampling methods in patients with type 2 diabetes. Issue 5 (4th November 2015) - Vu, Kim‐Nhien; Gilbert, Guillaume; Chalut, Marianne; Chagnon, Miguel; Chartrand, Gabriel; Tang, An
Abstract : Purpose: To assess the agreement between published magnetic resonance imaging (MRI)‐based regions of interest (ROI) sampling methods using liver mean proton density fat fraction (PDFF) as the reference standard. Materials and Methods: This retrospective, internal review board‐approved study was conducted in 35 patients with type 2 diabetes. Liver PDFF was measured by magnetic resonance spectroscopy (MRS) using a stimulated‐echo acquisition mode sequence and MRI using a multiecho spoiled gradient‐recalled echo sequence at 3.0T. ROI sampling methods reported in the literature were reproduced and liver mean PDFF obtained by whole‐liver segmentation was used as the reference standard. Intraclass correlation coefficients (ICCs), Bland–Altman analysis, repeated‐measures analysis of variance (ANOVA), and paired t ‐tests were performed. Results: ICC between MRS and MRI‐PDFF was 0.916. Bland–Altman analysis showed excellent intermethod agreement with a bias of –1.5 ± 2.8%. The repeated‐measures ANOVA found no systematic variation of PDFF among the nine liver segments. The correlation between liver mean PDFF and ROI sampling methods was very good to excellent (0.873 to 0.975). Paired t ‐tests revealed significant differences ( P < 0.05) with ROI sampling methods that exclusively or predominantly sampled the right lobe. Significant correlations with mean PDFF were found with sampling methods that included higher number of segments, total area equal or larger than 5 cm 2, or sampled both lobes ( P = 0.001, 0.023, and 0.002, respectively). Conclusion: MRI‐PDFF quantification methods should sample each liver segment in both lobes and include a total surface area equal or larger than 5 cm 2 to provide a close estimate of the liver mean PDFF. J. Magn. Reson. Imaging 2016;43:1090–1099.